Eco-Tourism and Sustainable Park Management: The TEMUAN experience in Gunung Ledang / Rohani Jangga ... [et al.] - Jangga, Rohani; Bakar, Ahmad Naqiyuddin; Yaakob, Ahmad Nawawi; Ali, Aliza; Mohd Salleh, Rosnani (2021)
According to UNWTO's classification, ecotourism means types of tourism that are wholly nature-based, include informative and interpretation features, normally, arranged by dedicated locally owned tour operators, and focuses on small groups of tourists. It reduces undesirable effects upon the natural and socio-cultural settings and aids to create commercial gains for host communities, organizations, groups, and relevant authorities handling natural zones with conservation objectives. Furthermore, it also offers other employment and salary opportunities for local communities and increases appreciation towards the conservation of natural and cultural assets, both among the local communities and tourists alike which inaugurates the concept of ‘community-based ecotourism’ (UNTWO, 2002). Community-based ecotourism is a type of ecotourism in which the local community has strong control over the management of ecotourism activities, as a result, some benefits remain within the community. Sustainable land use and ecotourism or nature-based tourism can either substitute or supplement current social, environmental, and economic activities, providing enough benefits to ensure residents’ commitment to conservation (Park, Zielinski, Jeong & Kim, 2020).